Evaluation of the structural performance of T-section beams with construction defects utilizing numerical analysis - Al-Kader A. Al Sayed, Abd; Al-jabali, Hebah Mohammad; Fahmy, Mohamed; Mohamed, Ghada N.; Bayoumi, El-Said Abd-Allah; Selouma, Tarek Ibrahim (Frontiers in Built Environment, 2024)
This study investigates recent incidents of slabs collapse in reinforced concrete T-beam constructions attributed to deficiencies in design detailing and execution. It employs numerical analyses using the finite element method in ANSYS software to model T-section beams, with validation against experimental tests. Subsequently, a parametric study is conducted to explore the behavior of T-section beams under various design and construction variables, including the spacing of secondary reinforcements in the slab, the diameter of secondary main reinforcements, and slab thickness. The numerical analysis results are found to align well with experimental findings. The parametric study highlights that the eccentricity of reinforcing bars in the secondary direction of the slab is more detrimental than in the main direction. Furthermore, using 10 mm diameter reinforcement in the slab, either in the main or secondary direction, enhances the slab's resistance to applied loads. Additionally, the study reveals that increasing the stiffness of the slab contributes to an improved resistance of the beam.